Pelayanan Pendidikan Keagamaan pada Masyarakat Minoritas di Kabupaten Tapanuli Utara, Sumatera Utara - Husen Hasan Basri (Badan Litbang dan Diklat Kementerian Agama RI, 2006)
This article depicts the implementation of religious educational service in minority society-involving the form and kinds of religious educational service given by minority society, the obstacles of its establishment and also its expectation to religious education in minority society. by taking a case in Tarutung, it is found that religious educational service in the region is depended on how far the creativity of moslem minority in managing the religious-educational service for themselves. in tarutung, the religious education service is organized by the Association of Moslem Tarutung. through this organization, the moslem minority of Tarutung carrying out the religious educational service such as reading al-Quran, writing al-Quran, and learning Shalat for fulfilling their community’s needs.